Transcriptomics-based investigation of molecular mechanisms underlying synergistic antimicrobial effects of AgNPs and Domiphen on the human fungal pathogen Aspergillus fumigatus - Du, Wenlong; Xu, Ruolin; He, Zhiqiang; Yang, Huan; Gu, Yufan; Liu, Yi (Frontiers in Microbiology, 2023)
Critically ill patients have higher risk of serious fungal infections, such as invasive aspergillosis (IA) which is mainly caused by the human fungal pathogen Aspergillus fumigatus. Triazole drugs are the primary therapeutic agents for the first-line treatment of IA, which could easily cause drug resistance problems. Here, we assess the potential of AgNPs synthesized with Artemisia argyi leaf extract and domiphen as new antifungal agents to produce synergistic antimicrobial effects on Aspergillus fumigatus, and dissect possible molecular mechanisms of action. Plate inoculation assays combined with drug susceptibility test and cytotoxicity test showed that the combination of AgNPs and domiphen has synergistic antimicrobial effects on A. fumigatus with low cytotoxicity. Gene Ontology (GO) enrichment analysis showed that AgNPs and domiphen inhibit the growth of A. fumigatus by suppressing nitrate assimilation, and purine nucleobase metabolic process and amino acid transmembrane transport, respectively. When the two drugs are combined, AgNPs has epistatic effects on domiphen. Moreover, the combination of AgNPs and domiphen primarily influence secondary metabolites biosynthesis, steroid biosynthesis and nucleotide sugar metabolism of A. fumigatus via Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. Furthermore, protein–protein interactions (PPI) analysis combined with validation experiments showed that the combination of AgNPs and domiphen could enhance the expression of copper transporter and inhibit nitrogen source metabolism. In addition, the synergistic antimicrobial effects could be enhanced or eliminated depending on exogenous addition of copper and nitrogen source, respectively. Taken together, the results of this study provide a theoretical basis and a new strategy for the treatment of IA.